2017
DOI: 10.3329/birdem.v7i2.32455
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, Risk Factors and Antibiotic Sensitivity Pattern of Extended-Spectrum Beta-Lactamase Producing Escherichia coli and Klebsiella pneumoniae Causing Urinary Tract Infection: Experience from a Tertiary Care Hospital of Bangladesh

Abstract: Background: Urinary tract infection (UTI) due to extended-spectrum beta-lactamase (ESBL) producing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
4
1
Order By: Relevance
“…8 Patients with diabetes mellitus and specially those with poor glycaemic control are at increased risk for infection with ESBL-positive organisms. 2,[15][16][17] The percentage of ESBL-positive organisms was higher in our study compared to some other international reports. 16,18 Inadvertent and nonjudicious use of antimicrobials may be one of the most important contributory factors for such findings in the present study.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…8 Patients with diabetes mellitus and specially those with poor glycaemic control are at increased risk for infection with ESBL-positive organisms. 2,[15][16][17] The percentage of ESBL-positive organisms was higher in our study compared to some other international reports. 16,18 Inadvertent and nonjudicious use of antimicrobials may be one of the most important contributory factors for such findings in the present study.…”
Section: Discussioncontrasting
confidence: 63%
“…Urinary tract infection (UTI) is the most common bacterial infection in adults and elderly population and patients with diabetes mellitus are at increased risk for UTI. [1][2][3] UTI, specially pyelonephritis may be complicated by bacteraemia and sepsis. 4,5 Antimicrobials remain the cornerstone for treatment of UTI and increasing antimicrobial resistance, specially extended-spectrum beta-lactamase (ESBL) producing organisms is an ever increasing problem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 In our study, we evaluated ESBL-positivity of organisms causing UTI as risk factor for AKI. UTI due to ESBL-positive organisms are increasingly been reported in Bangladesh [16][17][18] and Rahim MA et al 10 reported that diabetic females with long duration and poor glycaemic control are risk factors for UTI due to ESBL-positive organisms. Similar observation was reported in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with another study in India (30%) 33 . Alyamani et al 30 found that all E. coli isolates were sensitive to meropenem and Rahim et al 34 showed that all E. coli isolates were sensitive to impenem. Carbapenemes are now considered the last resort for treatment of infections caused by multidrug-resistant organisms.…”
Section: Discussionmentioning
confidence: 99%